How to Handle the Fiscal Crisis in Greece? Empirical Evidence Based on a Survey of Economic Experts - Martin Mosler; Niklas Potrafke; Markus Reischmann (Center for Economic Studies and ifo Institute (CESifo), 2019)
We asked economic experts polled by the CESifo World Economic Survey how to handle the fiscal crisis in Greece in the year 2015. The sample includes about 850 experts from 110 countries. We find systematic differences in experts' recommendations. Our results suggest that policy advice is related to an expert's personal and country-level attributes. Country-level characteristics, especially credit default swaps as a measure of fiscal stability, predict views on whether Greece should exit the eurozone. An expert's educational background, age and professional affiliation predict opinions on the credit programs of the International Monetary Fund. We propose that policymakers who seek balanced policy advice should consult experts from different countries and personal backgrounds.
Keywords: H63; C83; H12; F53; E42; F45; D72; 330; Greece; Grexit; experts' survey; public debt crisis; IMF; international organizations; policy advice